PENGARUH PEMBERIAN BERBAGAI KONSENTRASI KITOSAN PADA MEDIA KULTUR JARINGAN TERHADAP PERTUMBUHAN PLANLET KENTANG (Solanum tuberosum L.) - Nurhasanah, Nurhasanah; Fajarfika, Resti; Nurdiana, Dadi (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
Chitosan recently has been used in plant growth enhancement, as a growth promoter by increasing nutrient uptake, chlorophyll content, and photosynthesis rate. Tissue culture is the propagation of plants vegetatively in a short time and quickly. The results of the effect of chitosan application on potato planlets need to be reviewed. This study focuses on the effects of chitosan on potato plantlets and aims to determine the optimal concentration for their growth. This study used the experimental method of complete randomized design (CRD) with analysis using the Duncan Multiple Range Test (DMRT) method at a 5% level. There are 5 treatments namely, 0 mg/l, 5 mg/l, 10 mg/l, 15 mg/l and 20 mg/l and repeated 4 times. The results showed that chitosan significantly influenced the growth of potato plantlets. The best treatment was observed at a concentration of 20 mg/l, resulting in an average shoot emergence time was 5.25 days, a plantlet height was 8 cm, the number was leaves with 14 leaves, the number was roots 8.25 roots, and a root length of 8.5 cm.